Living in a Parallel Society: International Students and their Friendship Circles - Gomes, Catherine (Journal of International Students, 2020)
Whenever I write an opinion piece in any online media outlet about international students in Australia, I brace myself for the responses that appear in the comments section below the article. Often, a repeated complaint is that international students refuse to engage with local culture and society and hence keep to themselves by hanging out with co-nationals and speaking their native languages. While the general public in Australia does not engage in open conflict with international students over such grievances, they will instead discuss these anonymously online and with each other. Often these grievances have public airing through the media (e.g., Australian Broadcasting Corporation’s Four Corners episodes “Degrees of Deception,” 2015, and “Cash Cows,” 2019) or for political point scoring by Australian politicians (e.g., Senator Pauline Hanson of the right-wing, nationalist and anti-immigration party One Nation; Kainth, 2018).However, the reception international students receive in terms of the attitudes of the citizenry unsurprisingly does not assist in any way in helping them feel a sense of belonging to their host country Australia. In 2013 I interviewed 47 Asian international students in the Australian city of Melbourne on their self-perceived identities, social networks, and engagements with media and communication technologies, in order to understand how they create a sense of belonging for themselves while overseas (Gomes,2015, 2017). The results revealed that international students create a parallel society with other international students in order to cope with living in a foreign country without the familiarity of family or loved ones who they left behind. While this parallel society allows international students to create a sense of community in Australia, its side effect is a perceived distancing from local society.An International Student Parallel SocietyInternational students strongly identify themselves more so as international students than their nationality. A student from India, for instance, explained that while in Australia, he prefers to be identified as an international student rather than by his nationality. Taking this point further, a student from Vietnam explained that while he is proud of his nationality, he prefers not to reveal that he is from Vietnam for fear of any negative assumptions the citizenry make about Vietnamese people. These negative assumptions he felt, would then be translated into ways the citizenry might treat him.At the same time, the Asian international students also revealed that they did not consider ethnicity as significant to them. This was played out interestingly in how they viewed Asian Australians. Here the students felt that they had very little in common with Asians who were born or grew up in Australia. An international student from China explained that Australians of ethnic Chinese descent or ABCs (Australian-born Chinese) as she called them, were more Australian than they were Chinese. Meanwhile an Indian student undertaking postgraduate study vividly explained that he thought Indian-Australians were “not true Indians.” He said that while they may look like him, they were significantly different because he considered Indian-Australians culturally Australian and not culturally Indian. These responses are not surprising. In a separate study where colleagues and I surveyed 6,699 international students in Australia on who made up their friendship circles, we found that less than 1% of international students were friends with Australians who were of the same ethnicity as them (Gomes et al., 2015).International students identifying themselves according to their status as foreigners studying in Australia also provides itself to be a beacon for the development of friendships with other international students. The Asian international students interviewed revealed that their friendship circles were made up of fellow international students who were co-nationals in the first instance, which was followed by international students from the Asian region, and then, to a lesser extent, international students from elsewhere. These friendship circles contribute to the parallel society international students inhabit where they exist, occupy, and mimic Australian communities but do not integrate with them. For instance, international students may adopt and recreate Australian cultural practices that involve their friendship circles (e.g., having backyard barbeque parties) but do not integrate with Australian societies (e.g., the backyard barbeque parties are made up solely of fellow international students).In addition, forming friendships with fellow international students rather than with local communities has practical benefits. For instance, international students revealed that their local peers were unable to advise them on the everyday challenges they faced especially when they first arrive to Australia such as how to open bank accounts and where to find dependable Asian grocery shops. Clearly being friends with international students is important, if not necessary.ConclusionThe significance of international student friendships during their study experience is enduring, if not complex. While international students may form a parallel society, they do so in order to feel a sense of belonging in Australia rather than to Australia. Though this is unsurprising, the challenge that emerges affects those international students wanting to stay longer through further study, work, or permanently reside. Not integrating somewhat into Australian society may have consequences for students in terms of their long-term plans (e.g., employment) primarily because they have not tapped into local networks.